Cancers and erectile dysfunction: a Mendelian randomization study - Yang, Ge; Xiong, Yuanguo; Wang, Ziwen; Wang, Jingsong; Chen, Yongchuan; Zhang, Hong (Frontiers in Endocrinology, 2024)
Purpose Cancer often coexists with erectile dysfunction, yet the causal relationship between them remains unclear. This study aims to investigate the causal link between tumors and ED through Mendelian randomization. Method Data on 13 different cancers, including lung cancer, colorectal cancer, testicular cancer, lymphoma, esophageal cancer, pancreatic cancer, thyroid cancer, bladder cancer and brain cancer were collected from various databases. ED data, comprising 2,205 cases and 164,104 controls, were sourced from the FinnGen project. Primary methods for MR analysis included IVW, MR-Egger, weighted median, and weighted mode. Results IVW results revealed associations between colorectal cancer (OR=1.17;95% CI 1.02-1.13, p=0.0252), prostate cancer (OR=1.63;95% CI1.52-1.75, p<0.001) and liver cancer (OR=0.93;95% CI0.88 -0.99, p=0.012) with ED. Conclusion Mendelian randomization analysis supports that prostate cancer and colorectal cancer are associated with an increased risk of Erectile Dysfunction, whereas liver cancer is linked to a decreased risk of ED. No evidence suggests that ED contributes to an increased risk of prostate cancer.